A Review Natural Ventilation by Using Solar Chimney - Amit Sharma; Arvind Gwatiya; Arunesh Mishra; Rahul Rajput (International Journal of Electrical Power and Machine Systems, 2025)
A solar chimney is an effective and sustainable ventilation technology designed to enhance airflow within residential and commercial buildings by utilizing natural convection. Operating on principles like a traditional fireplace, a solar chimney harnesses solar energy to generate an upward air movement, creating a pressure difference that drives passive ventilation. The system comprises a vertical shaft, usually constructed with heat-absorbing materials, which captures solar radiation and heats the enclosed air. As the heated air rises, it is expelled from the structure, drawing in cooler outside air to replace it. This continuous airflow improves indoor air quality while reducing reliance on mechanical ventilation systems. In addition to passive ventilation, photovoltaic (PV) fans can be integrated with solar chimneys to enhance their efficiency. These fans use solar energy to actively expel superheated air, particularly from attic spaces, thereby reducing heat buildup. By maintaining lower indoor temperatures, solar chimneys decrease the load on HVAC systems, resulting in energy savings and improved thermal comfort. The effectiveness of a solar chimney is influenced by various factors, including its height, absorber material, orientation, and ambient weather conditions. Optimized design parameters can significantly enhance its performance, making it a viable solution for energy-efficient buildings. This paper provides a comprehensive review of solar chimneys, discussing their working principle, classification, and performance-influencing factors. Furthermore, it highlights the environmental and economic benefits of incorporating solar chimneys into modern architectural designs. As the need for sustainable and passive cooling solutions grows, solar chimneys offer a practical approach to reducing energy consumption and enhancing indoor environmental quality.
Keywords: Natural Ventilation; SCPP; SP-PCM; Solar Chimney; classification